2007
DOI: 10.1111/j.1365-2133.2007.08218.x
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis of aberrant gene expression in actinic keratosis: effect of the Toll-like receptor-7 agonist imiquimod

Abstract: The data show that profound gene expression changes occur in sun-exposed, nonlesional skin which progress further in AK lesions. The data also suggest that imiquimod may play a role in normalizing gene expression and cellular morphology in sun-damaged skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 72 publications
0
17
1
Order By: Relevance
“…This is particularly of interest for a TLR7 agonist-based vaccine, as there is precedence for the induction of TLR7 expression in several cell types, such as DCs and even keratinocytes, after Type I IFN stimulation. 47 Indeed, we have observed a dramatic up-regulation of TLR7 expression in the dLN of mice injected subcutaneously with recombinant IFN␣ (J.Z.O. and R.M.K., unpublished results, June 2010).…”
Section: Tlr7-elicited Cd8 T-cell Response 3035mentioning
confidence: 89%
“…This is particularly of interest for a TLR7 agonist-based vaccine, as there is precedence for the induction of TLR7 expression in several cell types, such as DCs and even keratinocytes, after Type I IFN stimulation. 47 Indeed, we have observed a dramatic up-regulation of TLR7 expression in the dLN of mice injected subcutaneously with recombinant IFN␣ (J.Z.O. and R.M.K., unpublished results, June 2010).…”
Section: Tlr7-elicited Cd8 T-cell Response 3035mentioning
confidence: 89%
“…If DNA damage results in inhibition of apoptosis of actinically damaged cells, further derangements might accumulate, resulting in the development of squamous cell carcinoma. Torres et al [112] examined the changes in gene expression occurring in sun-exposed nonlesional skin and in AK lesions. They found that imiquimod treatment was associated with partial or total reversal of the aberrant expression of some genes in AK, thereby demonstrating the ability of imiquimod to prevent the development of cancer.…”
Section: Current Use Of Tlr7/8 Ligands In Cancer Treatment and Cancermentioning
confidence: 99%
“…8 Treatment of AKs with imiquimod increases expression of genes associated with dendritic cell, macrophage, T-cell, and natural killer cell activation 9 ; down-regulates antiapoptotic genes 10 ; and reverses aberrant expression of some genes observed in AKs. 11 In addition to treating clinically apparent lesions, topical treatment with imiquimod can reveal and clear subclinical lesions. Imiquimod 5% cream is approved to treat AKs of the face or balding scalp using dosing regimens of 23/wk for a single 16-week course in the United States 12,13 and 33/wk for two sequential 4-week cycles separated by a 4-week, no-treatment interval in Europe.…”
mentioning
confidence: 99%